Software de entrenamiento auditivo para ingenieros de sonido (2016)
A Technical Ear Training software is proposed, using multimedia resources to promote interactive teaching. For this eight educational modules belonging to four specific topics are developed. Using the Python programming language and following the methodology proposed by the adapted RUP, giving as a result a lineal tutorial educational software. Usability tests are made according to the ISO/IEC TR 9126 – 4 standard. With the objective of have a sight of the user perception about certain items in the software. The project approach and the adapted RUP methodology allow developing the modules, and make the proposed product, however, the revision of some items in the developing chain is proposed with the purpose of getting a better final product. Finally, future work of the project is proposed including, migration of the programming language in the desktop application, also a project which test the impact of the software in students and finally the migration of the software into a web application. Grupo de Investigación: Modelamiento y Simulación Computacional. -- Línea de Investigación: Acústica y Procesamiento de Señales. -- Área: audio interactivo. -- Tema: entrenamiento auditivo técnico.